In vivo direct lentiviral gene therapy improves disease pathology in a mucopolysaccharidosis IVA murine model - Betul Celik; Estera Rintz; Shaukat Khan; Andrés Felipe Leal; Fnu Nidhi; Shunji Tomatsu (Molecular Therapy: Methods & Clinical Development, 2025)
Mucopolysaccharidosis IVA (MPS IVA) is an autosomal recessive disorder that causes the accumulation of keratan sulfate (KS) and chondroitin-6-sulfate in bone and cartilage. This results in progressive skeletal dysplasia, with no effective treatment available. Our study hypothesized that direct lentiviral vector (LV) gene therapy could produce active enzymes from transduced cells, impacting bone and cartilage lesions in MPS IVA. We developed LVs carrying the GALNS gene under three promoters: ubiquitous (CBh), collagen type II (COL2A1), and Mac-1 integrin subunit (CD11b). At the newborn stage and 4 weeks, Galns-knockout mice received intravenous injections at different doses (5 × 109, 1 × 1010, or 1 × 1011 TU/kg). Our analysis included vector copy numbers, enzyme activity, glycosaminoglycan levels, bone and heart pathology, and bone morphology. Results showed that intravenously infused high doses of LVs with the CBh promoter in newborn mice yielded the highest enzyme activity and normalized KS levels in plasma and tissues, improving bone and heart pathology without liver toxicity. We noted an increase in anti-GALNS antibodies, suggesting an immune response to the therapy. These findings underscore the potential of in vivo direct LV gene therapy as a promising approach for treating MPS IVA and similar skeletal disorders.